Cancer Immunotherapy: Comprehensive Mechanism Analysis of Mesoporous‐Silica‐Nanoparticle‐Induced Cancer Immunotherapy (Adv. Healthcare Mater. 10/2016). Issue 10 (May 2016) - Wang, Xiupeng; Li, Xia; Yoshiyuki, Kazuko; Watanabe, Yohei; Sogo, Yu; Ohno, Tadao; Tsuji, Noriko M.; Ito, Atsuo
Abstract : A plain mesoporous silica (MS) nanoparticle without any immunomodulatory molecules enhances anti‐cancer immunity in vivo. On page 1169, X.P. Wang, N. M. Tsuji, A. Ito and co‐workers show that a plain MS nanoparticle promotes both Th1 and Th2 immune responses, and enhances the effector memory of CD4 + and CD8 + T cell populations in the three most important immune organs (bone marrow, lymph node and spleen) of mice.